Pomen in cilji projektov ohranjanja dediščine prehrane - Godina-Golija, Maja (Etnolog. Nova vrsta (Ljubljana), 2018)
Unlike other cultural phenomena, the food of Europe's populations is a poorly researched area of life and culture, and few historical, ethnological, sociological, or anthropological studies have addressed the theme. Similarly, such studies are rare in Slovenia, and in the decades following the Second World War they were limited to addressing the festive and everyday dishes of the peasant population, while other themes related to food and nourishment, social groups, or individual areas were not researched. But these research aspects have become increasingly important and they are included in UNESCO's Convention for the Safeguarding of the Intangible Cultural Heritage. In the past decade, several major projects about food culture and culinary heritage have been carried out in European countries. This article addresses the Slovene projects about food, in particular the work of the researchers of the Institute of Slovene Ethnology, SRC, SASA, who in the past decade participated in studying food heritage as part of projects of the Register of the Intangible Cultural Heritage, Etnofolk and AlpFoodway.
Keywords: cultural heritage; food; food habits; hrana; kulturna dediščina; prehrambne navade; projects; projekti; raziskovanje; research; Slovenia; Slovenija